Radioactive waste curing method
Through a method including distillation, settlement, drying, ball milling and sintering, a cured uranium-containing ceramic with low porosity and high strength is formed, which solves the problem of easy corrosion in cement curing, significantly improves the radiation shielding effect and uranium fixation, and reduces the migration risk of radioactive substances.
Patent Information
- Application Number
- CN202510049645.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-13
AI Technical Summary
In the prior art, radioactive waste cured using cement is easily corroded by the environment, resulting in the dissipation of radioactive substances and unable to effectively prevent environmental pollution.
A method including distillation, settlement, drying, ball milling and sintering is adopted to mix the ceramic base material, lead compound and dry uranium powder, and through the steps of pressing, presintering and sintering, a low-porosity and high-strength cured uranium-containing ceramic is formed.
By reducing gas release during sintering, the porosity is reduced; the high Z characteristics of lead are used to significantly improve the radiation shielding effect; the design and sintering process of ceramic base material are optimized to ensure the high fixation and long-term stability of uranium, and the migration risk of radioactive substances is significantly reduced.
Smart Images

Figure CN119822795A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of radioactive contaminated material treatment, and in particular to a radioactive waste solidification method. Background Art
[0002] In the later stages of nuclear weapon charging or assembly, shaped explosives (including octogen) are often assembled with nuclear materials in the same "assembly chamber" or go through the same production line (such as hot pressing, machining, cleaning, etc.). It is physically difficult to completely isolate nuclear materials. Any tiny dust, debris, steam or attachments on the surface of the workpiece may carry radioactive nuclides. Once they come into contact with parts or washing solutions containing octogen, they will bring radioactivity into the washing solution. In a few modified explosives, special ammunition or experimental formulas, some compounds containing radioactive isotopes (such as certain trace radioactive isotopes used for detection, tracing or initiating special reactions) may be added. This practice will also lead to the generation of radioactive waste liquid in subsequent cleaning, recovery and recrystallization processes.
[0003] In order to produce octogen, DMSO (dimethyl sulfoxide) is needed in which octogen can be dissolved. Therefore, radioactive substances, such as residual uranium, are present in the DMSO washing water waste containing octogen.
[0004] In the existing technology, in order to prevent radioactive substances from escaping and polluting the environment, the radioactive substances need to be solidified. The usual method is to solidify them with cement and then throw them into the sea or bury them underground. However, conventional cement solidification has high porosity and is easily corroded by the seabed or underground environment, causing the radioactive substances solidified by cement to escape into the environment. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a radioactive waste solidification method, comprising:
[0006] S1, distilling the DMSO washing water waste liquid containing octogen, recovering DMSO, and obtaining a distillation residue;
[0007] S2, settling and drying the distillation residue to obtain dry uranium powder;
[0008] S3, mixing a ceramic base material, a lead compound and the dry uranium powder in a ball mill to obtain a mixed powder, placing the mixed powder in a mold, applying a pressure of 50 to 200 MPa to press a green sheet to obtain an embryonic body;
[0009] S4, pre-sintering the embryo body at a pre-sintering temperature in an inert atmosphere to obtain a pre-sintered embryo body;
[0010] S5. In an inert atmosphere, the pre-sintered green body is sintered at a temperature of 900-1250° C., then kept at that temperature for 2-4 hours, and cooled to room temperature to obtain a solidified uranium-containing ceramic.
[0011] In some embodiments, in S3, the ceramic base material includes, by mass, 35 to 45 parts of aluminum oxide, 25 to 35 parts of silicon dioxide, 5 to 15 parts of zirconium oxide, 3 to 7 parts of calcium oxide, 3 to 7 parts of iron oxide and 5 to 15 parts of adhesive.
[0012] In some embodiments, the binder includes one or more of clay, talc, slag or fly ash.
[0013] In some embodiments, in S3, the ratio of the ceramic base material, the lead compound and the dry uranium powder is (60-75): (10-25): (5-15) by mass.
[0014] In some embodiments, the lead compound includes: PbO, PbTiO 3 、PbO-SiO 2 One or more of .
[0015] In some embodiments, in S4, the pre-sintering temperature is 600-800° C., and the pre-sintering time is 12 hours.
[0016] In some embodiments, the initial sintering temperature is 900-950° C., the heating rate is 3-5° C. / min, the insulation temperature is 1200-1250° C., and the cooling rate is 2-5° C. / min.
[0017] In some embodiments, the S1 includes:
[0018] After diluting the DMSO washing water waste liquid containing octogen to the safe concentration limit of octogen, a mild oxidant was added stepwise at 30-60°C and stirred at a speed of 200 rpm;
[0019] The distillation is carried out under reduced pressure at a temperature of 40-60°C and -0.08MPa to -0.09MPa to recover DMSO and obtain a distillation residue.
[0020] In some embodiments, the mild oxidant includes one or more of ozone, persulfate, and hypochlorite.
[0021] In some embodiments, the S2 includes:
[0022] The pH of the distillation residue is adjusted to 6-7, phosphate is added in batches at a temperature of 55-65°C and stirred at a speed of 300 rpm. After reacting for 2 hours, the mixture is centrifuged at a speed of 4000 rpm to obtain a uranium-enriched precipitate;
[0023] The uranium enrichment sediment is vacuum dried for 8 to 24 hours, and the drying temperature is controlled at 80 to 120° C. to obtain dry uranium powder.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] 1. By drying the uranium solution and removing volatile components such as organic solvents and octogenins in the early stage, the gas released by organic decomposition during sintering is greatly reduced, which reduces the porosity of uranium-containing ceramics and further reduces the mobility of uranium and lead.
[0026] 2. By adding lead to the sintering raw materials, the ionizing radiation is continuously scattered and energy is lost between the uranium phase and the lead phase when passing through the solid body, thereby significantly improving the shielding effect.
[0027] 3. By adding lead to the sintering raw materials, the sintering temperature can be significantly reduced. The path of ionizing radiation is blocked by a large number of grains and high-Z phases, and the attenuation is more thorough.
[0028] 4. Lead can form a stable lead-based composite phase with the ceramic base material, and its chemical dissolution is significantly reduced, which not only ensures environmental safety but also maintains the long-term shielding ability of the material.
[0029] 5. By carefully designing and optimizing the formula of the ceramic base material and combining it with a suitable sintering process (including temperature, atmosphere, holding time, and heating and cooling rates), a ceramic solid body with low porosity, high strength, and a high degree of fixation on uranium can be obtained, greatly reducing the risk of migration of radioactive substances in the disposal environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the technical solutions of the embodiments of the utility model, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0031] Figure 1 This is a schematic diagram of the structure formed by the prepolymer, hard UV monomer and flexible UV monomer provided by the present invention after UV light curing;
[0032] Figure 2 A schematic diagram of the state of the modified organic silicon vesicles provided by the present invention on the surface of the cured film layer after photocuring;
[0033] Figure 3 This is a schematic diagram of the state of the solidified film layer provided by the present invention when it is rubbed by a force-applying object. DETAILED DESCRIPTION
[0034] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.
[0035] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0036] The present invention is now further described in conjunction with specific examples. The following examples are only for explaining the present invention, but do not constitute a limitation of the present invention. The test samples and test processes used in the following examples include the following (if the specific experimental conditions are not indicated in the examples, they are usually in accordance with conventional conditions or the conditions recommended by the reagent company; the reagents, consumables, etc. used in the following examples, if not otherwise specified, can all be obtained from commercial channels).
[0037] The present invention provides a radioactive waste solidification method, comprising:
[0038] S1, distilling the DMSO washing water waste liquid containing octogen, recovering DMSO, and obtaining a distillation residue;
[0039] S2, settling and drying the distillation residue to obtain dry uranium powder;
[0040] S3, mixing a ceramic base material, a lead compound and the dry uranium powder in a ball mill to obtain a mixed powder, placing the mixed powder in a mold, applying a pressure of 50 to 200 MPa to press a green sheet to obtain an embryonic body;
[0041] S4, pre-sintering the embryo body at a pre-sintering temperature in an inert atmosphere to obtain a pre-sintered embryo body;
[0042] S5. In an inert atmosphere, the pre-sintered green body is sintered at a temperature of 900-1250° C., then kept at that temperature for 2-4 hours, and cooled to room temperature to obtain a solidified uranium-containing ceramic.
[0043] By drying the uranium solution and removing volatile components such as organic solvents and octogenins in the early stage, the gas released by organic decomposition during sintering is greatly reduced and the porosity can be controlled.
[0044] During sintering, uranium oxide (UO 2 , U 3 O 8 ) or hydroxide UO 2 (OH) 2 Transformed into stable UO by high temperature 2 2+ Solid state; these uranium phases can undergo ion replacement or mechanical encapsulation with the ceramic matrix to form a dense "ceramic-lead-uranium" ternary solidified ceramic. Uranium mainly exists at the grain boundaries or inside the lattice, greatly reducing the dissolution and diffusion of uranium by external leaching solutions.
[0045] Lead has a large attenuation coefficient for high-energy photons such as X-rays and gamma rays. The large nucleus of lead and its outer electron cloud greatly increase the probability of photons undergoing Compton scattering and photoelectric effect, thereby reducing radiation penetration. By introducing lead compounds as one of the raw materials for sintering and solidifying uranium, PbO or PbTiO is introduced into ceramics. 3 Lead-based compounds such as uranium can form a "high-Z phase" at the microscopic level, causing the radiation to be scattered or absorbed more times inside the material, forming multiple scattering / absorption interfaces, which is equivalent to adding a "shielding microstructure" to the solid body. Since uranium itself is also a high-Z (92) element, the solid body already has a certain radiation attenuation effect. When the radiation passes through the solid body, it is constantly scattered and energy is lost between the uranium phase and the lead phase, thereby significantly improving the shielding effect.
[0046] At the same time, lead oxide or lead silicate glass can soften or partially melt in the range of 700-900°C, significantly reducing the sintering temperature, which is conducive to achieving overall densification at a relatively low temperature. The molten lead-based phase can wet the ceramic aggregate and the surface of uranium oxide, better "bonding" and sealing the gaps. In dense materials, the path of ionizing radiation is blocked by a large number of grains and high-Z phases, and the attenuation is more thorough.
[0047] In addition, when lead can form a stable lead-based composite phase with the ceramic base material, its chemical dissolution rate is significantly reduced. This ensures that lead will not be easily dissolved in the later stage (seawater, groundwater and other environments), which not only ensures environmental safety, but also maintains the long-term shielding ability of the material.
[0048] In some embodiments, in S3, the ceramic base material includes, by mass, 35 to 45 parts of aluminum oxide, 25 to 35 parts of silicon dioxide, 5 to 15 parts of zirconium oxide, 3 to 7 parts of calcium oxide, 3 to 7 parts of iron oxide and 5 to 15 parts of adhesive.
[0049] In this formula, alumina can form dense α-Al after sintering. 2 O 3 crystal phase or react with other components to form a spinel phase (such as MgAl 2 O 4 ) etc., to improve the material strength and reduce the porosity. 3+ ) and uranium ions (U 4+ , U 6+ Ion substitution may occur between SiO2 and Al2O3 or they may coexist in some new crystalline phases. 2 O 3 , CaO, etc. together form silicate glass or mullite (3Al 2 O 3 ·2SiO 2 ) and other crystalline phases, providing a silicate network that can "wrap" the uranium oxide particles and block their direct contact with the external environment. 2 (PSZ) has a phase transformation toughening mechanism, which reduces the overall microcracks after sintering and further reduces the porosity. 2 O 3 、SiO 2 The system can significantly improve the thermal shock resistance and fracture toughness of ceramics. Calcium oxide easily reacts with SiO at high temperatures. 2 、Al 2 O 3 Form various calcium aluminum silicates (such as calcium feldspar CaAl 2 Si 2 O 8 , calcite, etc.), which helps liquid phase sintering, reduces local melting point, and accelerates sintering densification. Iron oxide can improve the oxidation ability of the system and help high valence uranium (U 5+ / U 6+ )’s stable existence or phase transition.
[0050] When sintered at high temperature (900-1300℃), uranium ions (typically U 4+ or U 6+ ) can partially replace the metal cations in the base material lattice (such as Zr 4+ , Fe 3+ , Ca 2+ Once uranium enters the crystal lattice, it is not easily dissolved or carried away by the leaching solution (groundwater, brine, etc.), and the leaching rate is greatly reduced.
[0051] At the same time, during the sintering process, SiO 2The silicate glass phase or calcium aluminum silicate phase formed by components such as CaO can "encapsulate" uranium oxide particles in the glass-ceramic network. The porosity of the dense sintered body is extremely low (usually <5%, sometimes <2%), making it difficult for water and other fluids to penetrate or diffuse, greatly weakening the outward migration of radionuclides.
[0052] In addition, Al 2 O 3 、ZrO 2 The main crystal phase itself has high chemical inertness, and the dissolution rate is very low when immersed in acid, alkali or salt solution for a long time. 2 O 3 , CaO and other components will form a variety of composite oxides or crystalline phases (uranates, calcium uranates, iron uranates, zirconates, etc.) together with uranium ions under a suitable sintering atmosphere. These phases often have stable structures similar to those of natural minerals (such as perovskite structure, zircon structure or pyroxene / garnet structure) and can firmly bind uranium.
[0053] In summary, the use of this ceramic base material as a fixed uranium can:
[0054] (1) Improve sintering density, reduce porosity, and reduce leaching channels.
[0055] (2) It forms a stable ceramic crystal phase or glass-ceramic composite phase, which is extremely chemically inert and uranium ions are not easy to migrate.
[0056] (3) It can accommodate uranium in various valence states (U 4+ , U 6+ The uranium ions are anchored in the ceramic matrix by ion replacement or solid solution.
[0057] (4) Compared with traditional cement curing, high-temperature ceramicization has more advantages in long-term (decades to hundreds of years) stability and lower leaching rate.
[0058] By carefully designing and optimizing the above formula and combining it with a suitable sintering process (temperature, atmosphere, holding time, heating and cooling rates), a ceramic solid body with low porosity, high strength and a high degree of fixation for uranium can be obtained, greatly reducing the risk of migration of radioactive materials in the disposal environment.
[0059] In some embodiments, the binder includes one or more of clay, talc, slag or fly ash.
[0060] In some embodiments, in S3, the ratio of the ceramic base material, the lead compound and the dry uranium powder is (60-75): (10-25): (5-15) by mass.
[0061] Sintering is accomplished by mechanisms such as solid diffusion, liquid phase wetting and particle rearrangement. When lead compounds form a certain volume fraction of liquid phase at high temperature, they can wet and bond ceramic particles and uranium particles, playing a "lubricating / bonding" role. If the liquid phase ratio (caused by excessive lead compounds) far exceeds the optimal value, micropore collapse or stratification will occur locally in the sintered body, and uranium will also migrate and distribute unevenly in the low-viscosity liquid phase, and even lead will evaporate over a large area or enrich on the surface at high temperature, resulting in uneven internal quality and easy cracking of the finished product.
[0062] However, if the uranium powder content is too high, the skeleton phase of the ceramic base material will be destroyed by the excess uranium phase, forming a porous, low-strength sintered body, while greatly increasing the radiation activity and increasing the risk of secondary pollution.
[0063] Uranium (Z=92) and lead (Z=82) are both high-Z elements that can effectively absorb / scatter gamma rays and X-rays. The ceramic base material itself (relatively low in Z, mainly Al, Si, O, etc.) can only provide structural support and chemical stability, and has limited contribution to shielding high-energy photons. When the total proportion of lead compounds and uranium powder reaches 25-35% by mass, the solid body has a significant "high-Z phase distribution". This distribution forms multiple attenuation paths in the thickness direction of the material, thereby significantly weakening the transmission of rays. When the ratio of lead to uranium is appropriate (such as (2-1):1), the rays can undergo "lead-uranium-lead-uranium" multiple scattering / absorption inside the material, and the energy loss is amplified in stages; if the proportion of either lead or uranium is too low, the attenuation process is incomplete.
[0064] By setting the appropriate ratio, lead and ceramic matrix, uranium and ceramic matrix can form a multiphase structure that is as uniform as possible at high temperature, and lead and uranium can be locked in stable chemical phases respectively, which significantly reduces the risk of long-term leaching. At the same time, the "synergistic shielding" of high-Z lead + high-Z uranium significantly reduces gamma-ray / X-ray penetration.
[0065] In some embodiments, the lead compound includes: PbO, PbTiO 3 、PbO-SiO 2 One or more of .
[0066] In some embodiments, in S4, the pre-sintering temperature is 600-800° C., and the pre-sintering time is 12 hours.
[0067] By pre-sintering at this temperature, residual moisture and a small amount of organic binder can be removed and the porosity of the uranium-containing ceramic can be improved.
[0068] In some embodiments, the initial sintering temperature is 900-950° C., the heating rate is 3-5° C. / min, the insulation temperature is 1200-1250° C., and the cooling rate is 2-5° C. / min.
[0069] By controlling the sintering temperature parameters, the sintering energy consumption can be moderately reduced while ensuring the density and uniformity of the ceramic body, allowing the internal lattice to transition smoothly during the heating and cooling process and reducing stress concentration caused by excessive temperature gradients.
[0070] In some embodiments, the S1 includes:
[0071] S11, diluting the DMSO washing water waste liquid containing octogen to the safe concentration limit of octogen, adding a mild oxidant stepwise at 30-60° C., and stirring at a speed of 200 rpm;
[0072] S12, performing reduced pressure distillation at a temperature of 40-60°C and -0.08MPa to -0.09MPa to recover DMSO to obtain a distillation residue.
[0073] By diluting octogen to the safe concentration limit and adding mild oxidants step by step under mild conditions of 30-60°C, the detonation sensitivity of octogen (HMX) can be reduced, avoiding accidental deflagration during subsequent distillation or heating, and providing a safer and more stable raw material environment for subsequent uranium enrichment precipitation, ceramic sintering and other processes.
[0074] In some embodiments, the safe concentration limit of octogen is 5% by mass concentration.
[0075] By distilling at 40-60°C and -0.08MPa to -0.09MPa under reduced pressure, DMSO can be efficiently recovered and energy consumption can be reduced, which is helpful for resource recovery and waste liquid reduction.
[0076] In some embodiments, the mild oxidant includes one or more of ozone, persulfate, and hypochlorite.
[0077] In some embodiments, the S2 includes:
[0078] S21, adjusting the pH of the distillation residue to 6-7, adding phosphate in batches at a temperature of 55-65° C. and stirring at a speed of 300 rpm, reacting for 2 hours, and centrifuging at a speed of 4000 rpm to obtain a uranium-enriched precipitate;
[0079] S22. The uranium enrichment sediment is vacuum dried for 8 to 24 hours at a drying temperature of 80 to 120° C. to obtain dry uranium powder.
[0080] By adding phosphate in batches and stirring, uranium ions and phosphate radicals can form insoluble uranyl phosphate (UO 2 )(HPO 4 )·xH 2O), effectively capture and enrich uranium. Moderate drying temperature prevents uranium compounds from decomposing or sublimating at too high a temperature, and also avoids the risk of HMX residues caused by rapid temperature rise; it provides safe and uniform uranium source materials for subsequent high-temperature ceramic sintering.
[0081] Example 1
[0082] This embodiment provides a radioactive waste solidification method, specifically, comprising the following steps:
[0083] After diluting the DMSO washing water waste liquid containing octogen to the safe concentration limit of octogen, a mild oxidant was added stepwise at 45°C and stirred at a speed of 200 rpm;
[0084] Perform vacuum distillation at a temperature of 50°C and -0.085MPa to recover DMSO to obtain a distillation residue;
[0085] The pH of the distillation residue was adjusted to 6.5, phosphate was added in batches at a temperature of 60°C and stirred at a speed of 300 rpm. After reacting for 2 hours, the uranium-enriched precipitate was obtained by centrifugation at a speed of 4000 rpm.
[0086] The uranium enrichment sediment was vacuum dried for 16 hours at a drying temperature of 100°C to obtain dry uranium powder;
[0087] 700 g of a ceramic base material, 150 g of PbO and 100 g of dry uranium powder are mixed in a ball mill to obtain a mixed powder, the mixed powder is placed in a mold, and a 100 MPa pressure is applied to press a green body to obtain a green body, wherein the ceramic base material includes 280 g of aluminum oxide, 210 g of silicon dioxide, 70 g of zirconium oxide, 35 g of calcium oxide, 35 g of iron oxide and 70 g of talc;
[0088] Pre-sintering the embryo body at 700° C. in an inert atmosphere for 12 hours to obtain a pre-sintered embryo body;
[0089] In an inert atmosphere, the pre-sintered green body is sintered at a temperature of 925°C and then heated to 1200°C at a heating rate of 4°C / min, then kept warm for 3 hours, and then cooled to room temperature at a cooling rate of 3°C / min to obtain a solidified uranium-containing ceramic.
[0090] Example 2
[0091] This embodiment provides a radioactive waste solidification method, specifically, comprising the following steps:
[0092] After diluting the DMSO washing water waste liquid containing octogen to the safe concentration limit of octogen, a mild oxidant was added stepwise at 45°C and stirred at a speed of 200 rpm;
[0093] Perform vacuum distillation at a temperature of 50°C and -0.085MPa to recover DMSO to obtain a distillation residue;
[0094] The pH of the distillation residue was adjusted to 6.5, phosphate was added in batches at a temperature of 60°C and stirred at a speed of 300 rpm. After reacting for 2 hours, the uranium-enriched precipitate was obtained by centrifugation at a speed of 4000 rpm.
[0095] The uranium enrichment sediment was vacuum dried for 16 hours at a drying temperature of 100°C to obtain dry uranium powder;
[0096] 700 g of a ceramic base material, 150 g of PbO and 150 g of dry uranium powder are mixed in a ball mill to obtain a mixed powder, the mixed powder is placed in a mold, and a 100 MPa pressure is applied to press a green body to obtain a green body, wherein the ceramic base material includes 280 g of aluminum oxide, 210 g of silicon dioxide, 70 g of zirconium oxide, 35 g of calcium oxide, 35 g of iron oxide and 70 g of talc;
[0097] Pre-sintering the embryo body at 700° C. in an inert atmosphere for 12 hours to obtain a pre-sintered embryo body;
[0098] In an inert atmosphere, the pre-sintered green body is sintered at a temperature of 925°C and then heated to 1200°C at a heating rate of 4°C / min, then kept warm for 3 hours, and then cooled to room temperature at a cooling rate of 3°C / min to obtain a solidified uranium-containing ceramic.
[0099] Example 3
[0100] This embodiment provides a radioactive waste solidification method, specifically, comprising the following steps:
[0101] After diluting the DMSO washing water waste liquid containing octogen to the safe concentration limit of octogen, a mild oxidant was added stepwise at 45°C and stirred at a speed of 200 rpm;
[0102] Perform vacuum distillation at a temperature of 50°C and -0.085MPa to recover DMSO to obtain a distillation residue;
[0103] The pH of the distillation residue was adjusted to 6.5, phosphate was added in batches at a temperature of 60°C and stirred at a speed of 300 rpm. After reacting for 2 hours, the uranium-enriched precipitate was obtained by centrifugation at a speed of 4000 rpm.
[0104] The uranium enrichment sediment was vacuum dried for 16 hours at a drying temperature of 100°C to obtain dry uranium powder;
[0105] 700 g of a ceramic base material, 200 g of PbO and 150 g of dry uranium powder are mixed in a ball mill to obtain a mixed powder, the mixed powder is placed in a mold, and a 100 MPa pressure is applied to press a green body to obtain a green body, wherein the ceramic base material includes 280 g of aluminum oxide, 210 g of silicon dioxide, 70 g of zirconium oxide, 35 g of calcium oxide, 35 g of iron oxide and 70 g of talc;
[0106] Pre-sintering the embryo body at 700° C. in an inert atmosphere for 12 hours to obtain a pre-sintered embryo body;
[0107] In an inert atmosphere, the pre-sintered green body is sintered at a temperature of 925°C and then heated to 1200°C at a heating rate of 4°C / min, then kept warm for 3 hours, and then cooled to room temperature at a cooling rate of 3°C / min to obtain a solidified uranium-containing ceramic.
[0108] Comparative Example 1
[0109] This comparative example provides a radioactive waste solidification method, specifically, comprising the following steps:
[0110] After diluting the DMSO washing water waste liquid containing octogen to the safe concentration limit of octogen, a mild oxidant was added stepwise at 45°C and stirred at a speed of 200 rpm;
[0111] Perform vacuum distillation at a temperature of 50°C and -0.085MPa to recover DMSO to obtain a distillation residue;
[0112] The pH of the distillation residue was adjusted to 6.5, phosphate was added in batches at a temperature of 60°C and stirred at a speed of 300 rpm. After reacting for 2 hours, the uranium-enriched precipitate was obtained by centrifugation at a speed of 4000 rpm.
[0113] The uranium enrichment sediment was vacuum dried for 16 hours at a drying temperature of 100°C to obtain dry uranium powder;
[0114] 700 g of a ceramic base material and 100 g of dry uranium powder are mixed in a ball mill without adding PbO to obtain a mixed powder, the mixed powder is placed in a mold, and a 100 MPa pressure is applied to press a green body to obtain a green body, wherein the ceramic base material includes 280 g of aluminum oxide, 210 g of silicon dioxide, 70 g of zirconium oxide, 35 g of calcium oxide, 35 g of iron oxide and 70 g of talc;
[0115] Pre-sintering the embryo body at 700° C. in an inert atmosphere for 12 hours to obtain a pre-sintered embryo body;
[0116] In an inert atmosphere, the pre-sintered green body is sintered at a temperature of 925°C and then heated to 1200°C at a heating rate of 4°C / min, then kept warm for 3 hours, and then cooled to room temperature at a cooling rate of 3°C / min to obtain a solidified uranium-containing ceramic.
[0117] Comparative Example 2
[0118] This comparative example provides a radioactive waste solidification method, specifically, comprising the following steps:
[0119] After diluting the DMSO washing water waste liquid containing octogen to the safe concentration limit of octogen, a mild oxidant was added stepwise at 45°C and stirred at a speed of 200 rpm;
[0120] Perform vacuum distillation at a temperature of 50°C and -0.085MPa to recover DMSO to obtain a distillation residue;
[0121] The pH of the distillation residue was adjusted to 6.5, phosphate was added in batches at a temperature of 60°C and stirred at a speed of 300 rpm. After reacting for 2 hours, the uranium-enriched precipitate was obtained by centrifugation at a speed of 4000 rpm.
[0122] The uranium enrichment sediment was vacuum dried for 16 hours at a drying temperature of 100°C to obtain dry uranium powder;
[0123] 700 g of a ceramic base material, 150 g of PbO and 100 g of dry uranium powder are mixed in a ball mill to obtain a mixed powder, the mixed powder is placed in a mold, and a 100 MPa pressure is applied to press a green body to obtain a green body, wherein the ceramic base material includes 280 g of aluminum oxide, 210 g of silicon dioxide, 70 g of zirconium oxide, 35 g of calcium oxide, 35 g of iron oxide and 70 g of talc;
[0124] In an inert atmosphere, at a temperature of 925°C, the temperature is increased to 1200°C at a heating rate of 4°C / min, the embryo is sintered, then kept warm for 3 hours, and then cooled to room temperature at a cooling rate of 3°C / min to obtain a solidified uranium-containing ceramic.
[0125] Experimental detection method
[0126] The uranium-containing ceramics obtained in Examples 1-3, Comparative Examples 1 and 2 were tested, including porosity measurement, compressive strength measurement, uranium leaching rate and gamma ray attenuation rate.
[0127] Specifically, the detection method is as follows:
[0128] Porosity (apparent porosity) determination: Use deionized water to determine the apparent porosity. First measure the dry mass, then measure the immersed mass after vacuum degassing in water, and finally measure the suspended mass in water under water saturation. Calculate the apparent porosity and bulk density according to the standard formula, which is as follows:
[0129]
[0130] Among them, M wet is the impregnation mass, M dry is the dry mass, M sus The hanging mass.
[0131] Compressive strength determination: Use a universal testing machine to apply load at a constant loading rate until the sample collapses, record the maximum load and calculate the compressive strength based on the cross-sectional area of the sample.
[0132] Uranium leaching rate: After the sample was crushed by a pulverizer to meet the particle size requirements, it was mixed with TCLP leaching solution at a solid-liquid ratio of 1:20 and stirred for 18 hours. The leaching solution was collected by filtration and the uranium concentration was determined using an inductively coupled plasma mass spectrometer.
[0133] Gamma ray attenuation rate: Place the 137Cs radiation source and the scintillation detector at a fixed distance, first measure the count rate in the empty field state, then place a sample between the two and measure the count rate again, and compare the two measurement results to calculate the attenuation rate.
[0134] Experimental equipment
[0135] Electronic analytical balance used for mass measurement: Mettler Toledo-XS205
[0136] Vacuum degassing device: Shanghai Huate Technology HWT-5
[0137] Universal testing machine: Instron 5967
[0138] Crusher: Tianjin Test Instrument FZ-102
[0139] Filter: Sartorius 0.45μm PES filter membrane and filter device
[0140] Inductively coupled plasma mass spectrometer: Agilent 7900ICP-MS
[0141] ^137Cs radioactive source: Dongfanghongyuan DJG-137
[0142] NaI(Tl) Scintillation Detectors: ORTEC 905 Series
[0143] Experimental Results
[0144] Table 1 Detection results of uranium-containing ceramics
[0145]
[0146]
[0147] As shown in Table 1, in Example 2, the ratio of PbO: uranium powder is adjusted from 1.5:1 to 1:1, the total PbO amount remains unchanged, but the amount of uranium powder is increased (150g), which slightly increases the porosity (3.8%) and slightly decreases the strength (110MPa). In addition, due to the increase in uranium content in the material, the gamma attenuation rate increases slightly (96%), and synergistically shields radiation with PbO. Compared with Example 1, by implementing the ratio of Example 2, the ability of uranium-containing ceramics in shielding ionizing radiation is slightly improved, but the mechanical and leaching properties are slightly sacrificed.
[0148] In Example 3, compared with Example 1, the total proportion of PbO + uranium powder is higher, resulting in a porosity increase of 4.2% and a strength of 105 MPa. However, due to the synergistic shielding of high lead + high uranium (both high Z elements), the gamma attenuation rate is further improved (97%), and the uranium leaching rate can also be maintained at a low level (1.0×10 -5 g / m 2 ·d).
[0149] In Comparative Example 1, compared with Example 1, no lead compound (PbO) was added. The porosity increased (6.8%) without PbO, and the uranium leaching rate also increased (2.0×10 -5 g / m 2 d), the gamma attenuation rate dropped significantly to 82%, indicating that the addition of PbO not only helps densification (reduces porosity), but also improves the distribution of high-Z (82) elements in the material, thus enhancing radiation shielding.
[0150] In Comparative Example 2, compared with Example 1, the pre-sintering step was cancelled, and the final porosity was as high as 8.5%, the strength was greatly reduced (60MPa), and the uranium leaching rate and gamma decay rate were worse. This shows that the pre-sintering step helps to remove bound water, organic residues, etc., and allows the melt or crystal phase to be more evenly distributed in the subsequent sintering, reducing microcracks and pores.
[0151] In summary, it can be seen from the results in the table that a reasonable ratio of PbO to uranium powder (such as Examples 1, 2, and 3) and pre-sintering (Examples 1, 2, and 3) can significantly improve the density, compressive strength, uranium fixation, and radiation shielding ability of the solidified body.
[0152] Comparing the results of the two comparative examples (without adding PbO or canceling pre-sintering), the porosity, mechanical properties, uranium leaching rate and gamma attenuation rate are obviously deteriorated, indicating that the lack of these two factors will greatly reduce the material performance.
[0153] Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field and related fields without creative work should fall within the scope of protection of the present invention. The structures, devices and operating methods not specifically described and explained in the present invention are implemented according to the conventional means in the field unless otherwise specified and limited.
Claims
1. A method for solidifying radioactive waste, characterized in that: include: S1, distilling the DMSO washing water waste liquid containing octogen, recovering DMSO, and obtaining a distillation residue; S2, settling and drying the distillation residue to obtain dry uranium powder; S3, mixing a ceramic base material, a lead compound and the dry uranium powder in a ball mill to obtain a mixed powder, placing the mixed powder in a mold, applying a pressure of 50 to 200 MPa to press a green sheet to obtain an embryonic body; S4, pre-sintering the embryo body at a pre-sintering temperature in an inert atmosphere to obtain a pre-sintered embryo body; S5. In an inert atmosphere, the pre-sintered green body is sintered at a temperature of 900-1250° C., then kept at that temperature for 2-4 hours, and cooled to room temperature to obtain a solidified uranium-containing ceramic.
2. The radioactive waste solidification method according to claim 1, characterized in that: In S3, the ceramic base material includes, by mass, 35 to 45 parts of aluminum oxide, 25 to 35 parts of silicon dioxide, 5 to 15 parts of zirconium oxide, 3 to 7 parts of calcium oxide, 3 to 7 parts of iron oxide and 5 to 15 parts of adhesive.
3. The radioactive waste solidification method according to claim 2, characterized in that: The adhesive includes one or more of clay, talcum powder, slag or fly ash.
4. The radioactive waste solidification method according to claim 1, characterized in that: In S3, the ratio of the ceramic base material, the lead compound and the dry uranium powder is (60-75): (10-25): (5-15) by mass.
5. The radioactive waste solidification method according to claim 4, characterized in that: The lead compound includes one or more of PbO, PbTiO3, and PbO-SiO2.
6. The radioactive waste solidification method according to claim 1, characterized in that: In the step S4, the pre-sintering temperature is 600-800° C., and the pre-sintering time is 12 hours.
7. The radioactive waste solidification method according to claim 1, characterized in that: The initial sintering temperature is 900-950° C., the heating rate is 3-5° C. / min, the insulation temperature is 1200-1250° C., and the cooling rate is 2-5° C. / min.
8. The radioactive waste solidification method according to claim 1, characterized in that: The S1 includes: After diluting the DMSO washing water waste liquid containing octogen to the safe concentration limit of octogen, a mild oxidant was added stepwise at 30-60°C and stirred at a speed of 200 rpm; The distillation is carried out under reduced pressure at a temperature of 40-60°C and -0.08MPa to -0.09MPa to recover DMSO and obtain a distillation residue.
9. The radioactive waste solidification method according to claim 8, characterized in that: The mild oxidant includes one or more of ozone, persulfate and hypochlorite.
10. The radioactive waste solidification method according to claim 1, characterized in that: The S2 includes: The pH of the distillation residue is adjusted to 6-7, phosphate is added in batches at a temperature of 55-65°C and stirred at a speed of 300 rpm. After reacting for 2 hours, the mixture is centrifuged at a speed of 4000 rpm to obtain a uranium-enriched precipitate; The uranium enrichment sediment is vacuum dried for 8 to 24 hours, and the drying temperature is controlled at 80 to 120° C. to obtain dry uranium powder.
Citation Information
Patent Citations
process FOR SINTERING CERAMIC MATERIALS
BE771093A
Composition and method for radioactive irradiation protection
BG104952A
Chemically bonded ceramic radiation shielding material and method of preparation
CN101496112A
Heavy metal wastewater treatment technology, processing method thereof, and medicine production formula
CN103588319A
Waste leady CRT glass and high-level waste liquid coprocessing method
CN108417287A